Sustainable Product Innovation in Business Organizations: Theoretical Insights and Empirical Findings for Long-Term Value Creation - Kozludzhova, Katerina (European Journal of Sustainable Development, 2025)
The paper explores product innovation in business organizations by combining a theoretical review with empirical research findings. The theoretical framework is developed through in-depth review of academic literature that covers six areas of knowledge, related to the concept of “product innovation”. Building on literature insights, the conducted empirical study examines business organizations’ innovation activities and investigates their experiences, difficulties, and priorities across the various stages of the product innovation process. By empirically validating the literature findings, the paper provides a discussion on the identified key areas of study, outlining the interrelations between them, their practical implications, and potential ways for enhancing the product innovation process. The results reveal how business organizations assess product innovations, identify what they consider critical and highlight what difficulties they face throughout the innovation process, pointing to specific areas for improvement. The paper contributes theoretically by synthesizing diverse perspectives from the literature and presenting a structured view of product innovation that provides a conceptual foundation for the conduction of empirical studies. Practically, the paper offers insights into the organizations’ mindset and approaches towards managing product innovations, supporting managers to provide effective tools and practices that foster innovation performances. Finally, the study outlines opportunities for further research studies and necessary actions to improve the effectiveness of the product innovation process. Keywords: sustainable product innovation, literature review, empirical study, business organizations, innovation activities, challenges, survey results, innovation questionnaire